1985
DOI: 10.1152/ajpendo.1985.248.5.e624
|View full text |Cite
|
Sign up to set email alerts
|

Vascular perfusion: a novel means of studying oviduct function

Abstract: An in situ preparation for the combined vascular and luminal perfusion of the rabbit oviduct has been developed. Medium 199, gassed with 5% CO2 in O2 and supplemented with heparin, antibiotics, and 2.5% wt/vol dialyzed bovine serum albumin was infused into the ovarian artery at a rate of 1 ml/min. Krebs Ringer bicarbonate medium was recirculated through the lumen at a rate of 50 microliter/min. The ovary was perfused together with the oviduct, and the preparation is viable for up to 3 h. Equal concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Similar findings of high GLY levels were previously reported in bovine [2], ovine [22,23], rabbit [24], mare [25] and the mouse [26]. Leese and Gray, [27] reported that the secretion rate of GLY into the rabbit oviduct lumen was the highest of the amino acids and it comprised 70% of the amino acid pool in blastocysts. Aside from being a building block for protein synthesis, GLY has been shown to be one of the most effective organic osmoregulators for the mouse embryo [28][29][30].…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings of high GLY levels were previously reported in bovine [2], ovine [22,23], rabbit [24], mare [25] and the mouse [26]. Leese and Gray, [27] reported that the secretion rate of GLY into the rabbit oviduct lumen was the highest of the amino acids and it comprised 70% of the amino acid pool in blastocysts. Aside from being a building block for protein synthesis, GLY has been shown to be one of the most effective organic osmoregulators for the mouse embryo [28][29][30].…”
Section: Discussionsupporting
confidence: 86%
“…The morphology of cells cultured in 4-well plates is in accordance with that previously described by Van (Lodish et al, 1986 (Leese and Gray, 1985). …”
Section: Methodssupporting
confidence: 73%
“…However, the concen¬ tration of lactate in the pig oviduct was greater than that found in plasma in contrast to the findings of Holmdahl & Mastroianni (1965) for the rabbit oviduct. Leese & Gray (1985) investigated the source of these substrates in rabbit oviductal fluid, using a combined vascular and luminal perfusion system. They concluded that these substrates, except for lactate, are derived mainly from the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Using the technique of vascular perfusion, Leese & Gray (1985) demonstrated that the glucose and pyruvate that appeared in the lumen originated from blood whereas most of the lactate was derived from glucose within the oviductal wall.…”
Section: Introductionmentioning
confidence: 99%